Manejo de la diversidad cultivada en los agroecosistemas tradicionales = Managing crop diversity in traditional agroecosystems: Resúmenes del Simposio, 13-16 de Febrero del 2002, Mérida, Mexico = Proceedings of a Symposium, 13-16 February, Merida, Mexico - Chávez-Servia, J.L.; Arias Reyes, L.M.; Jarvis, Devra I.; Tuxill, J.; Lope-Alzina, D.; Eyzaguiree, C.; International Plant Genetic Resources Institute (2002)
Spanish and English in the same publication